Про хроматичне число натуральних модульних графів - Donets, G. P.; Shulinok, G. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The problem of chromatic number definition for a subclass of numerical graphs, namely natural modular graphs, is raised for the first time. A few affirmations are proved which allow defining the chromatic number of these graphs with the number of generatrixes not over three. To solve a general problem, a method of differences is proposed, possibilities of which are described and an example of its use is given.